Forecasting the Number of Jabodetabek Train Passengers Using ARIMA - Moerpradighta Prayreyka; Edwin Setiawan Nugraha; Mokhammad Ridwan Yudhanegara (Prosiding Sesiomadika, 2023)
This study aims to analyze a suitable forecasting model using ARIMA to help PT. KAI Indonesia in predicting the number of train passengers in Jabodetabek. This study uses the method of identifying forecasting patterns. Model selection is very important in forecasting because forecasting models are beneficial for forecasting using past data in the past. The sample used is the number of Jabodetabek train passengers from January 2014 to December 2016. The results show that the suitable forecasting method to predict the number of Jabodetabek train passengers is the ARIMA method (3,1,6). The results from this analysis can be used for considering to calculate operational costs and business development in the future.